Marthamyces manglicola, a new species (Ascomycota, Marthamycetaceae) on black mangrove from Cozumel Island, Mexico - Raymundo, Tania; García- Martínez, Yenitze; Martínez Pineda, Michelle; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2022)
Background and Aims: The genus Marthamyces is characterized by its orbicular to polygonal apothecia, immersed within the host tissue, erumpent from the substrate surface, by the hymenium with pruinose appearance due to the presence of small crystals on its surface and amongst the paraphyses, and by filiform, 0- to 3-septate ascospores. Members of this genus grow on leaves of plants throughout the world, mainly in the tropics and subtropics. The aims of this study are to describe and illustrate Marthamyces manglicola as a new species that grows on Avicennia germinans (black mangrove) from Cozumel Island and to elaborate a key to all species of the genus Marthamyces described until now.Methods: Specimens were collected on fallen leaves of black mangrove in Punta Sur Ecological Park, Cozumel Island Biosphere Reserve. Field data and morphological characteristics were recorded using the traditional techniques in mycology. The material was deposited in the ENCB herbarium of the Escuela Nacional de Ciencias Biológicas of the Instituto Politécnico Nacional.Key results: Marthamyces manglicola is characterized by its apothecia opening by 3-5 pruinose and yellowish white to pale yellow flaps, a hymenial surface greyish blue to dull blue in young specimens, fading to bluish white to pale blue or pale yellow in mature apothecia. Microscopically, it has paraphyses swelling slightly near the apex, with several short, finger-like projections and straight to slightly curved ascospores on release. A key to all described species of Marthamyces is presented.Conclusions: Marthamyces manglicola on Avicennia germinans (black mangrove) is the only species of this genus described from mangroves.